2012
DOI: 10.1007/s00737-011-0246-y
|View full text |Cite
|
Sign up to set email alerts
|

SUICIDALITY in the perinatal period: comparison of two self-report instruments. Results from PND-ReScU

Abstract: The aim of this study was to assess suicidality in a non-clinical sample during the perinatal period and to report suicidality rates in women with major or minor depressive episode (MmD), assessed with the SCID, during the perinatal period. Women (1,066) were recruited at the third month of pregnancy and followed until the 12th month postpartum (N = 500). Suicidality was assessed with the MOODS-SR and with item 10 of the EPDS at different time-points during the perinatal period. The period prevalence of suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 36 publications
5
43
1
1
Order By: Relevance
“…Moreover, this risk might vary by evaluation time. Studies employing the EDPS found decreasing rates from the third (5.4 %) to the sixth (4.1 %) to the eighth (3 %) month of pregnancy (Mauri et al 2012) and from the third (10.2 %) to the eighth (6.8 %) month (Evans et al 2001). We found that AD increases CSR by 5.60 times [95 % confidence intervals (CIs)=2.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, this risk might vary by evaluation time. Studies employing the EDPS found decreasing rates from the third (5.4 %) to the sixth (4.1 %) to the eighth (3 %) month of pregnancy (Mauri et al 2012) and from the third (10.2 %) to the eighth (6.8 %) month (Evans et al 2001). We found that AD increases CSR by 5.60 times [95 % confidence intervals (CIs)=2.…”
Section: Discussionmentioning
confidence: 83%
“…In a small sample of non-pregnant IPV survivors residing in a shelter, reports of intimate partner rape were associated with suicidal ideation though this relation was mediated by depression and post-traumatic stress disorder (Weaver et al 2007). In an Italian non-clinical sample of perinatal women, unemployment, low educational level, lifetime suicidality, previous suicide attempts and major depression during pregnancy were significantly associated with suicidality during pregnancy (Mauri et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The sequelae of completed suicide among new mothers are life altering and often debilitating for children and families. However, emerging evidence suggests that even postpartum suicidal ideation (SI), which occurs between 4%–8% in non-clinical (Mauri et al, 2012), 19%–30% in depressed clinical samples (Mauri et al, 2012; Wisner et al, 2013), and 9% in a primary care setting (Howard et al, 2011) is correlated with objectively-assessed disturbances across a variety of domains, including amplified parenting stress (Mauri et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For example, peripartum depressive symptoms and disorders, and a lifetime history of suicidal behavior were identified as strong psychiatric factors associated with postpartum SI (Mauri et al, 2012; Pope et al, 2013). In regards to contextual factors, SI shows great variability across postpartum.…”
Section: Introductionmentioning
confidence: 99%